Cooperation with Parents on Environmental Education of Preschool Children with Speech Disorders - Horopakha, Nataliia; Shadiuk, Olha; Frolenkova, Nadiia; Sotska, Olena; Proseniuk, Anzhela (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This article presents a comprehensive pedagogical technology for correctional and developmental work with parents and their preschool children with speech disorders. The purpose of this article is also to consider the change in parents’ attitude to the environmental education of a child with speech disorders. The project is designed to involve parents and increase their interest in the environmental education of preschoolers with speech disorders. It is investigated to what extent the involvement of parents and teachers in joint research projects increases competencies in terms of knowledge, abilities, and attitudes to educational processes. The article uses several methods of synthesis and analysis in research. The descriptive method and the experimental method were also used. The hypothesis is that using a comprehensive program involving parents for research and experimental activities in environmental education of preschool children with speech disorders promotes the more successful acquisition of knowledge about nature, improves therapy, and strengthens family relationships. In technology, attention is paid to the actual educational activities and the reflection of teachers’ and parents’ internal structures of competencies. The presented technology systematizes the instrumental-methodical, expressive (behavioral) aspects of teaching and raising a child with speech disorders and provides a universal basis for any intervention program to change attitudes and involve parents in educational work.